令 a=A1, b=A2, c=A3, ..., z=A26
且令 B = { 1, 2, 3, ..., 26 }
(y-a)(y-b)(y-c)*.....*(y-z)
= y^26
- (a+b+...+z)*y^25
+ (ab+ac+...+az+bc+bd+...+bz+...+yz)*y^24
- .............
+ abc*...*z
= y^26
- ΣAi*y^25 , i from 1 to 26
+ ΣAi*Aj*y^24 , ∀ i, j ∈ B 且 i≠j
- ΣAi*Aj*Ak*y^23 , ∀ i, j, k ∈ B 且 i, j, k皆不同
+ ............
+ A1*A2*A3*.....*A26
Ans:
y^26
- ΣAi*y^25 , i from 1 to 26
+ ΣAi*Aj*y^24 , ∀ i, j ∈ B 且 i≠j
- ΣAi*Aj*Ak*y^23 , ∀ i, j, k ∈ B 且 i, j, k皆不同
+ ............
+ A1*A2*A3*.....*A26
其中:
A1=a, A2=b, A3=c, ..., A26=z
B = { 1, 2, 3, ..., 26 }
This entry passed through the Full-Text RSS service — if this is your content and you're reading it on someone else's site, please read the FAQ at fivefilters.org/content-only/faq.php#publishers.